The role of ultrasound measurements and cosmetic scoring in evaluating the effectiveness of ethanol ablation in cystic thyroid nodules - (:unkn) unknown (John Wiley and Sons Inc, 2021)
Background: A minimally invasive approach has been adopted to treat benign cystic nodules in recent years, with ethanol ablation (EA) being used as a more common method in routine treatment. For this study, we aimed to investigate the change of nodule volumes and cosmetic scores before and after EA in benign thyroid nodules and the effectiveness of treatment. Therefore, ultrasound data and cosmetic scores of pure cystic, mixed-type and spongy-type benign thyroid nodules undergoing EA in the last two years were reviewed retrospectively. Methods: Archive scanning was performed for all cases that were proven benign by fine-needle aspiration biopsy (FNAB) and who underwent EA. In all 46 patients included in the study, thyroid FNAB was performed. Ultrasound images were available to assess the size and volumes at pretreatment and 3 and 6 months after EA. The cosmetic scores obtained before the procedure and at 6 months after EA were compared. Results: There was a statistically significant difference when the sizes and volumes of the nodules were compared at pretreatment, 3 and 6 months follow-up (P <.001). The mean pretreatment cosmetic score was 3.09, and at 6 months, it was 1.20, with a statistically significant difference (P <.001). Conclusions: Recently, a minimally invasive approach has been adopted in the treatment of benign cystic nodules, with ethanol ablation becoming more common in routine treatment. Therefore, ethanol ablation is very valuable in minimising complications that may arise from surgery. © 2021 John Wiley & Sons Ltd